APLIKASI TEKNOLOGI EKSPLORASI UNTUK MEMAHAMI KONDISI AIR TANAH DI DAERAH PADANG LUAS KABUPATEN TANAH LAUT - Prayogo, Teguh (Center for Environmental Technology, 2009)
Groundwater is water that comes from the ground. Groundwater comes from rain, snow, sleet, and hail that soaks into the ground. The water moves down into the ground because of gravity, passing between particles of soil, sand, gravel, or rock until it reaches a depth where the ground is filled, or saturated, with water. Groundwater is stored in the ground in materials like gravel or sand. Water can also move through rock formations like sandstone or through cracks in rocks. Groundwater is one of solution to overcome a problem of the need of drinking water in the PadangLuas Area, because the availability of surface water is not enough. The objective of research is finding out characteristic and condition of ground water in PadangLuas, Tanah Laut district. To meet the objective, it was applied method of geophysical technology, namely electrical resistivity method by injecting current into the ground through current electrodes that are grounded at the earth's surface and measuring the difference of the electrical potential between the potential electrodes. Based on data processing, modeling and interpretation, it was gained result concerning the existence of aquifer in PadangLuas area that is predicted to occupy between 30 Ã¢â‚¬â€œ 60 meter and 70 Ã¢â‚¬â€œ 120 meter depth.Ã‚Â Keywords : Groundwater, Electrical Resistivity